Hubungan Tingkat Kebugaran Jasmani dengan Status Kognitif pada Lansia di Desa Dukuh Dempok, Wuluhan, Jember - Salman Farisi; Hanny Rasni; Latifa Aini Susumaningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Cognitive impairment is a health problem that causes a large economic burden for elderly families and the community. Cognitive decline is a serious threat to the independence and quality of life of the elderly. The aim of this research was to analysis the relationship the level of fitness and the cognitive function status of the elderly. This research design was observational analytic research with Cross Sectional approach. There were 76 respondents which obtained by used Simple Random Sampling technique. Data collection used 6-MWT (6-Minutes Walking Test) and MMSE (Mini Mental Status Exam). Data analysis using statistical correlation spearman test with a significance level of 0.05. Ethical approval were obtained with serial number 321 / UN25.8 / KEPK / DL / 2019. The results showed that the elderly had a good fitness levels about 52.3% and had a normal cognitive status function of 87.1%. The statistical test result showed that the p value is 0.001; r = 0.474, which means there is a significant relationship between the level of physical fitness and the status of cognitive function. Factors that influence the cognitive function status of the elderly by maintaining physical fitness that can increase serum BDNF concentration. Improving physical fitness can be done by exercising like walking with a frequency of more than 4 times a week, with a duration of 20-30 minutes/day.